Digital Clipping Learning Media Based on the Practice of Pancasila Values in Theme 5 Sub-theme 1 for Class V Elementary School - Firnanda, Rizqi; Fajar Surya Hutama; Dyah Ayu Puspitaningrum; M. Sulthon Mashhud; Ridho Alfarisi (Universitas Pendidikan Ganesha, 2023)
21st century learning is closely related to the development of technology, information and communication. The lack of innovation in the use of technology in learning which is packaged into learning media causes learning to be less enjoyable, thus having implications for learning outcomes. The aim of this research is to develop valid, effective and practical digital clipping learning media based on the practice of Pancasila values for fifth grade elementary school students. This type of research is quantitative research with a research design developing the Borg and Gall model. The research subjects were 49 grade V elementary school students, 20 students were test subjects for product use. The data collection methods used were interviews, observation, questionnaires, learning outcomes tests, and documentation. Data collection instruments are interview guides, observation sheets, questionnaires, questions and documents. The data analysis techniques used are product validation, instrument reliability testing, analysis of the distinguishing power index and difficulty index, effectiveness testing and practicality testing. The results of this research are digital clipping learning media based on the practice of Pancasila values. The conclusion is that this research produces an educational product, namely digital clipping learning media which has been tested for validity, effectiveness and practicality, so that it can be used in the learning process.